Intravitreal dexamethasone implants for the treatment of refractory scleritis combined with uveitis in adult-onset Still's disease: a case report. Issue 1 (December 2016) - Ahn, Seong; Hwang, Sun; Lee, Byung
Abstract Background Adult-onset Still's disease is a systemic inflammatory disease which presents with uveitis and scleritis in the eye. Intravitreal dexamethasone implants are used for the treatment of refractory uveitis. Case presentation A 19-year-old woman diagnosed to have adult-onset Still's disease for fevers, joint pain, and a salmon-colored bumpy rash presented with scleritis and uveitis in the left eye. Topical and systemic steroids with oral methotrexate failed to control the inflammation. We performed intravitreal injections of dexamethasone implants for side effects of steroid and refractory ocular inflammation. The therapy resulted in improvements in the patient's uveitis with reductions in scleral vessel engorgement and redness. There was no recurrence of uveitis or scleritis during 4 months following treatment. Conclusions Intravitreal injections of dexamethasone implants may result in clinical improvements of refractory scleritis combined with uveitis.